LEGAL STATUS OF DOMAIN NAMES IN THE LEGISLATION OF UKRAINE AND DOCTRINAL SOURCES - Filinovych, Valeriya V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: determination of the legal nature of domain names, identification of deficiencies in their legal regulation in national legislation, and the formulation of relevant proposals to improve this legislation. The methodological basis of the research comprises philosophical, dialectical, historical, formal logical, synergetic methods. Results: doctrinal sources, as well as legislation, do not have a unified approach to determining the essence and place of domain names, as the author of the article points out. Also, in this scientific work, various approaches to this issue are considered, and the author’s recommendations are given on solving the problem that has arisen concerning domain names and their place in the legal relation. Discussion: improvement of the national legislation of Ukraine in the sphere of domain names regulation; development of a procedure for resolving conflicts related to the clash of rights to domain names with rights to other means of individualization of participants in civil turnover.